The role of glyphosate in RR soybean production and seed quality - Albrecht,L.P. (2014)
This study aimed to evaluate the production components and quality of RR soybean seeds (Roundup Ready®), after application of increasing rates of gliphosate. Field experiments were conducted in Mandaguari, Paraná, during two seasons. Treatments consisted of five doses of glyphosate. All applications were performed once, between development stages V4 and V5. The experiment was arranged in a completely randomized block design, with four replicates. Data were subjected to analysis of variance, and when significant, t-tests and a regression analysis were applied to verify the behavior of the treatments. The physiological and sanitary quality, yield and mass of one thousand seeds were evaluated. The results indicated that seed quality can be adversely affected by glyphosate, and also showed a probable reduction in yield components with increasing rates of application.